Age-period-cohort analysis of schizophrenia incidence in China and Japan from 1990 to 2021: long-term trends and risk changes - Hao, Yifan; Zhao, Hu; Xu, Zhixian; Feng, Yu; Bai, Ruhai; Gu, Hui (Frontiers in Psychiatry, 2025)
BackgroundSchizophrenia represents the psychiatric disorder with the highest per capita social cost globally, with East Asia bearing a disproportionate burden of schizophrenia episodes and associated disability-adjusted life years. This study aimed to comprehensively evaluate the long-term trends in schizophrenia incidence in China and Japan from 1990 to 2021.MethodsData were extracted from the Global Burden of Disease 2021 study and systematically analyzed using age-period-cohort modeling approaches to disentangle temporal trends.ResultsThe overall drift values for schizophrenia incidence were -0.25% (95% CI: -0.28% to 0.23%) in China and 0.30% (95% CI: 0.20% to 0.41%) in Japan. In China, local drift values were positive only in the 10–25 age group and negative across all other age groups. For Japanese males, local drift values were negative except in the 15–25 age group. The longitudinal age curves for schizophrenia in the both countries demonstrated a characteristic inverted “V” shape, with peak incidence occurring in the 20–24 age group. Regarding period effects, China showed an overall decreasing trend that reversed toward unfavorable outcomes after 2014, while Japan also exhibited a decreasing trend recently, albeit with greater fluctuations. The cohort effect in China displayed a U-shaped pattern, whereas Japan showed an overall upward trend with a slight midpoint decrease, in the middle, followed by a sharp rise in risk for cohorts born after 2000.ConclusionDespite established mental health initiatives in both China and Japan, schizophrenia risk is increasing among youth cohorts in both countries. This finding underscores the urgent need for both nations to develop more effective, demographically targeted approached to improve mental health outcomes across different population segments.